EFEKTIVITAS PROGRAM PELATIHAN PUBLIC SPEAKING DALAM MENINGKATKAN RASA PERCAYA DIRI SISWA - Sulviana Sulviana; Mulyadi Mulyadi; Rifka Faried; Aisyah Aisyah; Afdalul Hairil (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Low self-confidence in public speaking remains a common challenge among high school students, often characterized by communication anxiety, hesitation in expressing opinions, and difficulty regulating emotions when speaking before an audience. This condition highlights the need for structured interventions that can strengthen students' self-confidence through systematic public speaking training. This study aimed to evaluate and empirically examine the effectiveness of a structured public speaking training program in improving the self-confidence of eleventh-grade students at SMAN 18 Makassar. The study employed a quantitative approach using a One-Group Pretest–Posttest Design involving 18 students selected through purposive sampling. Data were collected using questionnaires, observations, and interviews, and analyzed through descriptive statistics and thematic analysis. The findings revealed that the mean self-confidence score increased from 56 in the pre-test to 82 in the post-test, with a gain score of 26 points. All self-confidence indicators improved, with eye contact showing the highest increase (35.8%). Observations and interviews further confirmed that students became more confident, managed communication anxiety more effectively, and participated more actively during classroom activities. Therefore, the structured public speaking training proved effective in enhancing students' self-confidence and can be implemented as a sustainable non-academic development program in schools. ABSTRAK Rendahnya rasa percaya diri siswa ketika berbicara di depan umum masih menjadi permasalahan yang banyak ditemukan di lingkungan sekolah menengah, ditandai dengan kecemasan, keraguan menyampaikan pendapat, serta ketidakmampuan mengendalikan emosi saat tampil di depan kelas. Kondisi tersebut menunjukkan perlunya intervensi yang mampu meningkatkan kepercayaan diri melalui pelatihan public speaking yang terstruktur. Penelitian ini bertujuan mengevaluasi dan menguji secara empiris efektivitas program pelatihan public speaking dalam meningkatkan kepercayaan diri siswa kelas XI SMAN 18 Makassar. Penelitian menggunakan pendekatan kuantitatif dengan desain One Group Pretest-Posttest Design yang melibatkan 18 siswa melalui teknik purposive sampling. Data dikumpulkan menggunakan angket, observasi, dan wawancara, kemudian dianalisis secara deskriptif dan tematik. Hasil penelitian menunjukkan skor rata-rata kepercayaan diri meningkat dari 56 menjadi 82 dengan gain score sebesar 26 poin. Seluruh indikator kepercayaan diri mengalami peningkatan dengan rata-rata 28,0%, terutama pada kemampuan menjaga kontak mata. Hasil observasi dan wawancara mengonfirmasi bahwa siswa menjadi lebih berani berbicara, mampu mengendalikan kecemasan, dan lebih aktif berpartisipasi. Dengan demikian, pelatihan public speaking terbukti efektif meningkatkan kepercayaan diri siswa serta layak diimplementasikan sebagai program pengembangan kompetensi nonakademik di sekolah.